(untitled) (Fiep Bulletin - online, 2014)
Background and purpose: To assess the two-year postpartum prevalence of urinary incontinence and pelvic floor muscle dysfunction and the factors responsible for them. Subjects: Cross-sectional study with 220 women with previous two-year elective cesarean section or vaginal childbirth. Methods: Urinary incontinence symptoms were asked, pelvic floor muscle dysfunction was assessed by digital palpation and perineometer. Results: Two-year urinary incontinence prevalence following vaginal childbirth and cesarean section was 17% and 18.9%. Risk factor for pelvic floor muscle dysfunction was weight gain during pregnancy (digital palpation: OR: 0.874; 95% CI: 0.775-0.985 and perineometer: OR: 0.184; 95% CI: 0.038-0.895). Body mass index less than 25 kg/m2 and normal pelvic floor muscle were protective factors against urinary incontinence. Gestational urinary incontinence increased the risk for two-year postpartum urinary incontinence. Conclusion: Gestational urinary incontinence was a crucial precursor of postpartum urinary incontinence. Weight gain during pregnancy increased the risk of later pelvic floor muscle dysfunction, and elective cesarean section was not a preventable action for urinary incontinence.